Blend de óleos essenciais como alternativa aos antimicrobianos melhoradores de desempenho na dieta de leitões em fase de creche - Grando, Maiara Ananda (2021)
The ban on the use of antimicrobial growth promoters (AGP) in animal production demands the search for alternatives that can sustain current productivity and that are considered safe. Essential oils (EO) are plant-derived additives that have shown positive effects on animal health and growth. Therefore, the aim of this study was to investigate the effects of an EO blend on growth performance, occurrence of diarrhea (OD), hematological and blood biochemical profile, intestinal morphometry, morphology and microbiology, relative weight, length, and pH of the content of organs, and hepatic antioxidant status of weaning pigs, as an alternative to conventional AGP. One hundred and thirty-five crossbred entire male piglets, with an average initial body weight of 7.09 ± 0.29 kg and an average final body weight of 23.82 ± 1.53 kg were used. Animals were divided based on a randomized block design into five treatments, with nine replicates of three piglets per experimental unit. Treatments were a negative control diet (NC), NC + 125 mg/kg of enramycin 8%, as antimicrobial growth promoter (AGP), NC + 100, 200 and 400 mg/kg of the EO blend composed of thymol, cinnamaldehyde, D-limonene and carvacrol (EO100; EO200; EO400). Basal diets were divided into four phases (pre-starter I, pre-starter II, starter I and starter II) and throughout the experimental period the growth performance variables such as average daily body weight gain (ADBWG), average daily feed intake (ADFI), average final body weight (AFBW), and feed efficiency (FE), were evaluated, as well as the OD. At the end of the pre-starter II and initial II phases, blood was collected from 18 animals of each treatment to assess blood hematological and biochemical profiles. At the end of the experimental period, six piglets from each treatment were selected for evaluation of intestinal microbiology, morphology and morphometry, organs relative weight, length, and pH of its contents, and hepatic antioxidant status. The data obtained were submitted to the Student-Newman-Keuls (SNK) and Tukey mean comparison tests, at 5% probability. In the initial phase II, the FE was better for treatments EO400 and EO200, when compared to EO100 (p<0.05). During the total period, OE400 was more effective in controlling OD than NC and EO100 (p<0.05). Among the blood variables, in the pre-starter II phase, lower values of total proteins were observed for NC (p<0.05). Furthermore, NC had a lower value of plasma proteins when compared to AGP, and EO100 had a lower mean corpuscular volume (MCV) than EO400 (p<0.05). In the starter II phase, higher MCV and lower mean corpuscular hemoglobin and red blood cells were observed for EO400 when compared to EO100 (p<0.05). In this same phase, higher levels of band neutrophils were obtained for AGP, similar to EO400 and EO200 (p<0.05). The addition of AGP and EO to the diets increased (p<0.05) the hepatic activity of the antioxidant enzyme superoxide dismutase. The other parameters evaluated were not influenced (p>0.05) by the dietary treatments. In conclusion, the addition of the EO blend to the diets of weaning piglets was able to positively influence the OD, hematological and blood biochemical profile, and the hepatic antioxidant status of the animals, without any impair to the growth performance, intestinal morphometry, morphology and microbiology, relative weight, length, and pH of the content of organs, showing that it can be used as an alternative to conventional AMD.